2014
DOI: 10.1371/journal.pone.0115879
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for Adverse Events Reduces the Length of Hospital Stay in Patients Admitted to Otolaryngology Ward: A Single Arm Intervention Study

Abstract: BackgroundTo determine whether adverse events extend the duration of hospitalization, and to evaluate the effectiveness of medical intervention in ameliorating adverse events and reducing the prolonged hospital stay associated with adverse events.MethodsA single arm intervention study was conducted from October 2012 to March 2014 in the otolaryngology ward of a 614-bed, university-affiliated hospital. Adverse events were monitored daily by physicians, pharmacists and nurses, and recorded in the electronic medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…The incidence of ADR is an important cause of morbidity and mortality, and has considerable influence on the cost for medical management and hospitalization . However, the occurrence and severity of ADR varies among wards, patient populations and therapeutic strategies …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of ADR is an important cause of morbidity and mortality, and has considerable influence on the cost for medical management and hospitalization . However, the occurrence and severity of ADR varies among wards, patient populations and therapeutic strategies …”
Section: Introductionmentioning
confidence: 99%
“…2,4,5 However, the occurrence and severity of ADR varies among wards, patient populations and therapeutic strategies. [6][7][8] We previously reported that several adverse events, including microbial infection, oral mucositis, odynophagia, neutropenia, insomnia and constipation, were significant risks for prolongation of hospital stay in patients with head and neck cancer who were admitted to the otolaryngology ward. 8 Notably, pharmacotherapies for amelioration of such adverse events were effective in reducing the duration of hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a unique manifestation of oral mucosal injury has been documented within the past 5 years in association with mammalian target of rapamycin (mTOR) inhibitors 8, 9, 10. This latter toxicity has now emerged as one of the most common adverse events associated with targeted cancer therapies 11, 12, 13, 14, 15, 16, including in women being treated for invasive breast cancer 17, 18.…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, subgroup analysis of the study of 121 patients who received radiotherapy for head and neck cancer indicated that pharmaceutical interventions to ameliorate the symptoms of such adverse events significantly reduce the hospitalization period. 9 Moreover, subgroup analysis of the study of 121 patients who received radiotherapy for head and neck cancer indicated that pharmaceutical interventions to ameliorate the symptoms of such adverse events significantly reduce the hospitalization period.…”
Section: Discussionmentioning
confidence: 99%
“…9 Notably, pharmacotherapies for the cure of such adverse events are effective in reducing the duration of hospital stay in patients with head and neck cancer. 9 Notably, pharmacotherapies for the cure of such adverse events are effective in reducing the duration of hospital stay in patients with head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%